Effect of constrained fibers on electromechanical actuation of charge-controlled dielectric elastomers. (26th February 2018) - Zhang, Junshi; Chen, Hualing; Li, Dichen
Abstract: As is known, electromechanical deformation of voltage-controlled dielectric elastomers (DEs) is significant but is susceptible to pull-in and snap-through instabilities, while the large stable deformation can be achieved by spraying charge on DE surfaces, i.e., charge-controlled DEs. In this article, we investigate the effect of constrained fibers on electromechanical actuation of charge-controlled DEs by involving two special deformation modes: uniaxial tension and pure shear state. The coupled effects between the geometrical sizes and the mechanical tensile force of the charge-controlled DEs are also explored. The research results indicate that, different from voltage-controlled DEs, the electromechanical stretch of charge-controlled DEs with constrained fibers does not always show a beneficial merit with respect to that of the charge-controlled DEs without constrained fibers.